Lymphocytic variant of hypereosinophilic syndrome: A report of seven cases from a single institution. Issue 3 (11th March 2020) - Hu, Zhihong; Wang, Wei; Thakral, Beenu; Chen, Zhining; Estrov, Zeev; Bueso‐Ramos, Carlos E.; Verstovsek, Srdan; Medeiros, L Jeffrey; Wang, Sa A.
Abstract: Background: Lymphocytic variant of hypereosinophilic syndrome (L‐HES) is a subtype of HES driven by cytokines produced by clonal T‐cells. Due to the rarity of its occurrence and challenges in diagnosis, this subtype of HES is under recognized. Methods and Results: We report seven patients with L‐HES, diagnosed from a group of 136 patients who were referred to our institution for the work‐up of hypereosinophilia. The clinical presentation, symptoms and signs were heterogeneous and uncharacteristic; indistinguishable from idiopathic HES. Flow cytometry immunophenotypic analysis revealed aberrant T‐cells in all patients, with a Th2 immunophenotype, CD2 + CD3−CD4 + CD5 + CD7dim+/−CD8− in six of seven (86%) cases. CD10 was partially expressed in one of seven (14%) cases, and clonal TCR gene rearrangement was detected by PCR in five of seven (71%) patients. All patients were treated with corticosteroids and two of seven (29%) patients received anti‐IL5 antibody therapy. With a median follow‐up time of 7.5 years (2.3–14.1 years), one (11%) patient developed peripheral T‐cell lymphoma 6.1 years after the initial diagnosis of L‐HES and responded well to chemotherapy. All patients were alive at the last follow‐up. Conclusion: In conclusion, a combination of flow cytometry immunophenotyping and molecular analysis allows the identification of aberrant T‐cells, facilitating a diagnosis of L‐HES in patients with eosinophilia. A correct diagnosis is essential for the proper management of these patients.